Prevalence and associated factors affecting pelvic floor disorder among women in Ethiopia: A systematic review and meta-analysis - Tefera Belsty Mihretie; Wubshet Nebiyu Mogess (PLoS ONE, 2025)
Introduction Pelvic floor disorders are a global health problem affecting millions of women, particularly in developing countries. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence and common factors affecting pelvic floor disorders among women in Ethiopia. Method Databases such as PubMed, Google Scholar, SCOPUS, Hinari and DOAJ were systematically searched to identify eligible studies. The quality of included studies was assessed using Joanna Briggs Institute checklist. Data extraction was performed using Endnote and analyzed using STATA 17 version. To examine possible heterogeneity between studies, the I² test was used. A DerSimonian and Laird random effects model was used to derive pooled prevalence and odds ratio. Funnel plot and Egger’s test were used to detect possible publication bias. This review was registered under PROSPERO ID 2024CRD42024572321. Result A total of 8 eligible studies with 9703 participants were included in this systematic review and meta-analysis. The pooled prevalence of pelvic floor disorders among women in Ethiopia was 25% (95% CI 0.20–0.30). Pelvic organ prolapse was the most common pelvic floor disorder 28% (95% CI 0.13–0.43), followed by urinary incontinence 19% (95% CI 0.09–0.29). Vaginal delivery greater than or equal to five (AOR: 4.02.95% CI 1.87–8.79), place of delivery at home (AOR: 1.02.95% CI 0.35–2.98), history of episiotomies (AOR: 2.69.95% CI 0.54–13.49) and women who married under 18 years of age (AOR: 1.32. 95% CI 0.37–4.77) showed a significant association with the prevalence of pelvic floor disorders. Conclusion Pelvic organ prolapse is the most common pelvic floor disorder in Ethiopia. Vaginal deliveries, home deliveries, episiotomies and early marriage were identified as factors affecting pelvic floor disorder in Ethiopia.